Eigenfunction expansion for symmetric multiparameter problems - Konstantinov, A. Yu.; Stadnyuk, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
An abstract theorem on the expansion in generalized eigenvectors of multiparameter problems for Hermitian operators is established. The applications to differential operators are considered.